FEATURES OF TRANSFORMATIONS OF RED BLOOD CELLS IN CHILDREN WITH BRONCHIAL ASTHMA - E. N. Suprun; S. V. Suprun; O. E. Guseva; M. A. Loschenko; T. V. Pivkina; E. A. Savitskaya; S. V. Anuriev; V. A. Osmolkina; S. S. Braga (Медицинская иммунология)
Increase prevalence of bronchial asthma (BA) is noted recently. That’s why its treatment remains an urgent problem in allergology. Along with congenital atopy, a significant role in formation and development of a disease is given to hyperreactivity of bronchial tubes which is connected with a alterations of their epithelial membranes. However, sampling of bronchial epithelium cells is carried out by means of bronchoscopy with a biopsy which is an invasive procedure. Therefore, bronchial hyperreactivity is a relative contraindication for this intervention. Meanwhile, there exists a non-invasive method of integrated cellular membrane assessment.Analysis of membrane transformation in erythrocytes which do not have their own metabolism may be an informative model of cellular membranes in the organism in general. We have examined 52 persons (2 to 17 years old) including 20 children with bronchial asthma and the comparison group comprising 32 healthy ageand sex-matched children. Percentage of spontaneous red blood cells (RBC) transformation in the patients was carried out by means of light microscopy in whole blood smears made of native cell suspension. Children with bronchial asthma (2.6%) exhibited more frequent occurrence of destructive RBC forms than in healthy children (0.8%, р < 0.05), with predominance of stomatocytes (0.55% and 0,1%) which were >5-fold more common in children with bronchial asthma (р < 0.05). Respectively, transitional forms were significantly more often encountered in control group (39.9% against 34.12%), р < 0.05. Bronchial asthma is characterized by stomatocytic way of RBC transformation.An indicator of compensatory transformation (a ratio of transitional-to-destructive RBC forms) seems to represent an integrative criterion for membrane ability of reversal to normal state. Children suffering from bronchial asthma (р < 0.05) have decreased levels of this compensatory transformation indicator as compared to healthy children (2.1 and 3.5 respectively), as shown in our study. Evaluation of external respiratory function is chosen as the objective parameter defining severity of bronchial asthma.A strong reverse correlation (R = -0.82) is shown between FEV1 index and quantity of spheroids (transitional forms), as well as significant direct correlation (R = 0.76) between FEV1 and indicator of compensatory transformation level. Hence, we noted that the patients with bronchial asthma have disturbances of erythrocyte transformation, when compared to healthy children. There is a direct dependence between severity of a disease and expressed changes of RBC membrane transformation.